Comparison of modeling jet exhaust on a complex model of science and application fluent 6.3 - Синило, К.В. (Proceedings of National Aviation University (archive), 2009)
There are represented results of numerical simulations due to program Fluent 6.3 of fulfilled gases jet from aircraft engine. Jet was released close the ground in wind direction. Considered task is corresponding to wall slipsream.